Affectivity for inclusion in early childhood education (Research, Society and Development, 2023)
The present article, aims, to discuss the importance of affection for inclusion in early childhood education. It is recognized by the literature reviewed that affection interferes with a person's interpersonal relationships with peers, adults, and the rest of the world. The child is expected to engage in numerous interactions throughout their time at school where affectivity will be present. To enable children, adolescents, and adults to develop new knowledge, it is also important to understand objectively how affectivity contributes to the learning process. Affectivity is essential for educational results, because the children's words make it clear that it plays a significant role in the learning process, which is based on mutual respect, dialog, and, especially, mutual love. It was found that there is a strong relationship between the ideas, and that once the educator is aware of the ideas and their practical implications in the theories presented, he/she can enhance the relationship between teaching and learning, making the growth of an individual more positive and effective.